Assessment of Youth Water Polo Players’ Swimming Sprint Potential: A New Approach to Building an International Model - Andrea Perazzetti; Antonio Tessitore; Mehmet Zeki Özkol; Nebojša Novoselac; Milivoj Dopsaj (Journal of Functional Morphology and Kinesiology, 2025)
Background: To cope with their horizontal swimming phases, water polo players use different swimming techniques, such as specific variants of the crawl swimming style. Thus, this study aimed to investigate the swimming skills of young water polo players. Methods: An all-out 25-m sprint swimming test in crawl style was completed by 273 international youth water polo players (age = 14.0 ± 0.8 yrs) in two modalities: basic crawl with the head in the water (25CHeadIN), and a crawl performed while dribbling the ball (25CBall). Results: We registered an average time of 14.79 and 15.64 s for 25CHeadIN and 25CBall, respectively, in which the ball dribbling increased to 5% of the swimming time. A swimming skill index (25CSIC) was calculated to account for differences in ball dribbling speeds, which, considering our international sample and in the absence of previous data, we could speculate as the first international standard value for 14-year-old male water polo players competing at international level. The averaged values for 25CSI and 25CSIC were 0.94 ± 0.04 (a.u.) and 1.52 ± 0.15 (a.u.), respectively. Factor analysis indicated that swimming with and without the ball are structurally distinct technical skills, highlighting the specificity of these water polo players’ abilities. Moreover, the study shows significant differences (p < 0.05) between players from different countries and despite some limitations, its results provide valuable insights for the assessment and development of sprint swimming skills in youth water polo players. Conclusions: In summary, the findings of this research provide practical implications for training, player selection, player development and the optimization of youth water polo player performance.